2021
DOI: 10.3390/plants10081614
|View full text |Cite
|
Sign up to set email alerts
|

Study of Postharvest Quality and Antioxidant Capacity of Freshly Cut Amaranth after Blue LED Light Treatment

Abstract: Freshly cut vegetables are susceptible to microbial contamination and oxidation during handling and storage. Hence, light-emitting diode technology can effectively inhibit microbial growth and improve antioxidant enzyme activity. In this paper, the freshly cut amaranth was treated with different intensities of blue light-emitting diode (LED460nm) over 12 days. Chlorophyll content, ascorbic acid content, antioxidant capacity, antioxidant enzymes activity, the changes in microbial count, and sensorial evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…With respect to the storage time, our results showed that the individual phenolic constituents reached the highest values at M1–M3, after which a significant reduction (by 19–60%) became noticeable at M6. The current phytochemical data could imply that post-harvest metabolic activation reactions, well-described in numerous fresh fruits and vegetables [ 21 , 22 , 23 ], might still occur in dried comfrey materials for a certain period of time (up to 2–3 months), before enzymatic or physico-chemical degradative processes become prevalent (up to six months). Previously, it has only been shown that the harvest time can have a significant influence on the phytochemical composition of fresh comfrey roots.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the storage time, our results showed that the individual phenolic constituents reached the highest values at M1–M3, after which a significant reduction (by 19–60%) became noticeable at M6. The current phytochemical data could imply that post-harvest metabolic activation reactions, well-described in numerous fresh fruits and vegetables [ 21 , 22 , 23 ], might still occur in dried comfrey materials for a certain period of time (up to 2–3 months), before enzymatic or physico-chemical degradative processes become prevalent (up to six months). Previously, it has only been shown that the harvest time can have a significant influence on the phytochemical composition of fresh comfrey roots.…”
Section: Discussionmentioning
confidence: 99%
“…The positivity rate showed that the contamination of ready-to-eat vegetables by P. aeruginosa was significantly higher than that of other types of food, such as cooked meat products, cold ready-to-eat foods, and drinking water which was 6.25%, 17.65%, and 1.19%, respectively ( Cai et al, 2015 ). This favorable rate of P. aeruginosa was due to dominant flora of vegetable plant saprophytic bacteria ( Jin et al, 2021 ). Pseudomonas aeruginosa carried by water sources and raw materials may also cause contamination at all points in the sequence of vegetable irrigation, circulation, and clean vegetable processing in an open environment and eventually contaminate ready-to-eat vegetable products.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of P. aeruginosa along the food chain could cause gastrointestinal infections ( Fakhkhari et al, 2022 ). More importantly, P. aeruginosa is the dominant spoilage bacteria and has the strongest spoilage potential in vegetable that are stored under aerobic conditions ( Dharmarha et al, 2019 ; Jin et al, 2021 ). Additionally, the shelf life of ready-to-eat vegetables is seriously affected by P. aeruginosa , which will cause great economic losses ( Godova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, far-red LED lighting enhanced the leaf senescence. Although in the latest study [93] blue LED lighting did not lead to interesting findings, Jin et al [95] showed that, under refrigerated conditions, blue LEDs (30 µmol m −2 s −1 ) can increase the shelf life of amaranth baby leaves for an additional 2-3 d at 4 • C, increasing the antioxidant capacity when compared to lower doses, such as 10 and 20 µmol m −2 s −1 .…”
Section: Postharvest Uv and Visible Spectrum Illumination Strategies ...mentioning
confidence: 96%